Atributos do solo em função de tratos culturais em lavouras de cafeeiro conilon no sul do estado do Espírito Santo - Effgen, Teóphilo André Maretto (2006)
The work had as objective to evaluate, in different sampling site, the attributes of soils cultivated with conilon coffee trees crops under different management in the South of Espírito Santo State. Soil samplings were taken in the depths of 0.00 0.20 m